Media trend match - Clive Corder (Communicare)
The author argues that there is an increasing need for qualitative criteria for media selection in advertising. A number of guidelines for qualitative media selection are proposed and illustrated by an explica. tion of Media Trend Match, a media selection system which has been developed in South Africa. A large number of factors are taken into account in media selection for advertising. Most of these factors can be expressed in quantitative terms, for example circulation figures, incidence of radio and TV sets, coverage, cumulative reach and frequency over a stated time period, and audience composition in terms of demographics and user group categories. Other quantitative factors, such as page readership, Starch and DART scores, and thoroughness of reading and viewing, may be considered. Much less attention is, however, paid to qualitative factors, and these are usually evaluated subjectively. The qualitative aspects involved in determinants of media selection should not be underestimated. While most advertisers and media users seem to recognise that the medium can have a considerable influence over the ways m which a message is interpreted, limited interest is nevertheless paid to the psychological characteristics of media audien- ces. In a recently published paper, Caffyn (1980) noted that the use of statistically reliable measures of social attributes to describe people, is a useful and perhaps even a necessary way of distinguishing between various media exposure groups. But even when this is recognised as important, very little qualitative data, on which media selection deci- sions could logically be based, is presently available. Media Trend Match, a system which has been developed in South Africa, can provide guidelines for qualitative media selection. The present paper is a brief description of Media Trend Match